1999
DOI: 10.1038/10518
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian heparanase: Gene cloning, expression and function in tumor progression and metastasis

Abstract: Heparan sulfate proteoglycans interact with many extracellular matrix constituents, growth factors and enzymes. Degradation of heparan sulfate by endoglycosidic heparanase cleavage affects a variety of biological processes. We have purified a 50-kDa heparanase from human hepatoma and placenta, and now report cloning of the cDNA and gene encoding this enzyme. Expression of the cloned cDNA in insect and mammalian cells yielded 65-kDa and 50-kDa recombinant heparanase proteins. The 50-kDa enzyme represents an N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
946
1
9

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 736 publications
(979 citation statements)
references
References 46 publications
22
946
1
9
Order By: Relevance
“…This confirmed earlier findings that heparanase mRNA is highly expressed in metastatic rat and human breast cancer cell lines in vitro, whereas the nonmetastatic variants express little or no heparanase mRNA. [14][15][16] The incidence of heparanase expression in primary cancers was significantly higher in patients with lymph node metastases than those without metastases. Two of the essential processes required for metastasis are angiogenesis and tumor cell invasion of the basement membrane and extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirmed earlier findings that heparanase mRNA is highly expressed in metastatic rat and human breast cancer cell lines in vitro, whereas the nonmetastatic variants express little or no heparanase mRNA. [14][15][16] The incidence of heparanase expression in primary cancers was significantly higher in patients with lymph node metastases than those without metastases. Two of the essential processes required for metastasis are angiogenesis and tumor cell invasion of the basement membrane and extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…A Volume of 7 ml of total RNA isolated from approximately 10 000 cells were mixed with 1 ml of oligo-(dT) [12][13][14][15][16][17][18] primer, 1 ml of random hexamers primer (N 6 ), and 1 ml of 10 mM dNTPs in a total volume of 10 ml. They were heat denaturated at 651C for 5 min, and then chilled in ice.…”
Section: Rt-pcr Of Microdissected Cellsmentioning
confidence: 99%
“…Indeed, previous studies have suggested a role for heparanase in various pathophysiological conditions, including tumor metastasis (Escobar Galvis et al, 2007;Vlodavsky and Friedmann, 2001), experimental autoimmune disease (Lider et al, 1989), amyloidosis (Li et al, 2005) and delayed type hypersensitivity (DTH) reactions . A role for heparanase in tumour metastasis is supported by the strong correlation between levels of heparanase expression and metastatic potential of B16 melanoma (Vlodavsky et al, 1999) and T lymphoma (Goldshmidt et al, 2002b) cells. Further, it has been shown by RNA interference that suppression of heparanase expression ameliorates DTH reactions as well as reduces lung colonization of B16 melanoma cells (Edovitsky et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Three other sites of transcription initiation, at nucleotides À330, À101, and À98 (sites A and B/C in Fig. 6), have also been described for the human gene (Hulett et al, 1999;Vlodavsky et al, 1999;Dong et al, 2000;Jiang et al, 2002). Alternative transcriptional start sites do not alter the putative translation initiation start codon, which remains unaffected and localized inside exon 2.…”
Section: Expression Of Heparanase In X Laevis Is Driven By Two Promomentioning
confidence: 67%
“…Not surprisingly, given the different transcription sites in the promoters of the two species, the human promoter was not functional in any of the Xenopus systems studied. Yet, certain aspects of the exonintron distribution appear to be conserved between the two species, including: (i) 14 coding exons; (ii) the presence of a spliced exon 1 constitutive of a 5 0 untranslated region (UTR); (iii) alternative transcription initiation sites with the start translation codon localized in exon 2 (Hulett et al, 1999;Vlodavsky et al, 1999;Dong et al, 2000;Jiang et al, 2002;Bertolesi et al, 2008); and (iv) the presence of cis-elements in the first intron able to drive heparanase expression in both species, as we showed in this study.…”
Section: Developmental Expression Of Heparanase 2667mentioning
confidence: 99%